Role of Lipids of the Evergreen Shrub Ephedra monosperma in Adaptation to Low Temperature in the Cryolithozone - Vasiliy V. Nokhsorov; Svetlana V. Senik; Valentina E. Sofronova; Ekaterina R. Kotlova; Alexander D. Misharev; Nadezhda K. Chirikova; Lyubov V. Dudareva (Plants, 2022)
Lipids are the fundamental components of cell membranes and they play a significant role in their integrity and fluidity. The alteration in lipid composition of membranes has been reported to be a major response to abiotic environmental stresses. Seasonal dynamics of membrane lipids in the shoots of Ephedra monosperma J.G. Gmel. ex C.A. Mey. growing in natural conditions of permafrost ecosystems was studied using HPTLC, GC-MS and ESI-MS. An important role of lipid metabolism was established during the autumn-winter period when the shoots of the evergreen shrub were exposed to low positive (3.6 °C), negative (−8.3 °C) and extremely low temperatures (−38.4 °C). Maximum accumulation of phosphatidic acid (PA), the amount of which is times times greater than the sum of phosphatidylcholine and phosphatidylethanolamine (PC + PE) was noted in shoots of E. monosperma in the summer-autumn period. The autumn hardening period (3.6 °C) is accompanied by active biosynthesis and accumulation of membrane lipids, a decrease of saturated 34:1 PCs, 34:1 PEs and 34:1 PAs, and an increase in unsaturated long-chain 38:5 PEs, 38:6 PEs, indicating that the adaptation of E. monosperma occurs not at the level of lipid classes but at the level of molecular species. At a further decrease of average daily air temperature in October (−8.3 °C) a sharp decline of PA level was registered. At an extreme reduction of environmental temperature (−38.4 °C) the content of non-bilayer PE and PA increases, the level of unsaturated fatty acids (FA) rises due to the increase of C18:2(Δ9,12) and C18:3(Δ9,12,15) acids and the decrease of C16:0 acids. It is concluded that changes in lipid metabolism reflect structural and functional reorganization of cell membranes and are an integral component of the complex process of plant hardening to low temperatures, which contributes to the survival of E. monosperma monocotyledonous plants in the extreme conditions of the Yakutia cryolithozone.